Cancer Theranostics: A Versatile Theranostic Nanoemulsion for Architecture‐Dependent Multimodal Imaging and Dually Augmented Photodynamic Therapy (Adv. Mater. 21/2019). Issue 21 (21st May 2019) - Zhang, Yifan; Bo, Shaowei; Feng, Tao; Qin, Xialing; Wan, Yilin; Jiang, Shanshan; Li, Chunxiao; Lin, Jing; Wang, Tianfu; Zhou, Xin; Jiang, Zhong‐Xing; Huang, Peng
Abstract : In article number1806444, Zhong‐Xing Jiang, Peng Huang, and co‐workers synthesize an amphiphile to emulsify perfluorohexane into a nanoemulsion for multimodal‐imaging‐guided photodynamic therapy. The rupture of the nanoemulsion in tumor tissues can render opposite changes of the photoacoustic and fluorescence/magnetic resonance signals of the amphiphile. Furthermore, the inner perfluorohexane can responsively release oxygen as a fuel supply for highly efficient cancer photodynamic theranostics.